Unusual presentation of Kimura's disease involving the parotid gland in an Indian male: a case report and review of literature - David P Tauro; K Kiran Kumar; S Shibani; Kaveri Hallikeri (Journal of Oral Biology and Craniofacial Research)
ABSTRACT: Kimura's disease (KD) is a rare chronic inflammatory disorder that involves the subcutaneous tissues and occurs predominantly in the head and neck region, frequently associated with regional lymphadenopathy or salivary gland involvement. Although, not an uncommon condition in the Asian countries, it is quite rare among the occidental civilization and in the western countries is more commonly diagnosed among Asian migrants. Kimura's disease is sometimes confused with angiolymphoid hyperplasia with eosinophilia, which occurs in the superficial skin of the head and neck region. The classical features of angiolymphoid hyperplasia with eosinophilia are characterized by a triad of painless subcutaneous masses in the head and neck region, blood and tissue eosinophilia, and markedly elevated immunoglobulin E (IgE) levels. Here, we report a case of a 33-year-old Indian male with KD who presented with unilateral nodular swelling in the right parotid region. The diagnosis was based on characteristic histopathologic findings in conjunction with peripheral eosinophilia and elevated serum IgE levels